GE_GERICHTE P/2616/2014 vom 15. September 2015 - GE Cour de justice (2015)
FIXATION DE LA PEINE; PRONOSTIC ; PEINE PÉCUNIAIRE; INDEMNITÉ(EN GÉNÉRAL); AVOCAT | CP.34 ; CP.36.1 ; CP.41.1 ; CP.42.1 ; CP.47 ; CP.49.1 ; CPP.436.2